Gas-cell atomic clocks for space: new results and alternative schemes - Affolderbach, Christoph; Breschi, Evelina; Schori, Christian; Mileti, Gaetano (My University, 2006)
We present our development activities on compact Rubidium gas-cell atomic frequency standards, for use in space-borne and ground-based applications. We experimentally demonstrate a high-performance laser optically-pumped Rb clock for space applications such as telecommunications, science missions, and satellite navigation systems (e.g. GALILEO). Using a stabilised laser source and optimized gas cells, we reach clock stabilities as low as 1.5·10-12 τ-1/2 up to 103 s and 4·10-14 at 104 s. The results demonstrate the feasibility of a laser-pumped Rb clock reaching < 1·10-12 τ-1/2 in a compact device (<2 liters, 2 kg, 20 W), given optimization of the implemented techniques. A second activity concerns more radically miniaturized gas-cell clocks, aiming for low power consumption and a total volume around 1 cm3 , at the expense of relaxed frequency stability. Here miniaturized “chip-scale” vapour cells and use of coherent laser interrogation techniques are at the heart of the investigations.
, 2006